INFLUENCING FACTORS OF INNOVATION IN SURAKARTA CITY GOVERNMENT, CENTRAL JAVA, INDONESIA - Perdani Budiarti Hayuningtyas; Jun Matsunami; Bakti Setiawan (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
After the fall of the New Order regime in 1998, Indonesia changed from a centralized government system to decentralization. By the issuance of Grand Design of Bureaucratic Reform Year 2010-2025 in 2010, public sector innovation cannot be neglected due to the needs for new, innovative, adaptive, and entrepreneurial approaches to bureaucratic reform. Many innovations have been produced in local government to improve their performance. Surakarta City Government is recognized as an innovative city, produce innovative programs, often become examples of good practice in public sector innovation, and appointed as Innovation Laboratory in 2017. This study aims to describe public sector innovation in Surakarta City Government and what factors influencing it. The study was conducted using qualitative research methods with a case study approach and collecting data from interviews and document analysis. The findings of this study reveal that most of the public sector innovation in Surakarta City are ICT based innovation and provides benefits in improving the performance of local governments. Even though there is shifting leadership, the visionary leadership supported by upper-middle managers still plays a crucial role in encouraging innovation in local government, followed by supportive regulations from both central and local government, as well as participation and strong cooperation between sectors. Further, this study draws some recommendations to create an integrated policy to strengthened, evaluate, and maintain the sustainability of public sector innovation in the local government. The local government may provide opportunities to collaborate with NGOs to create public sector innovation.